2015
DOI: 10.1016/j.cell.2015.05.015
|View full text |Cite
|
Sign up to set email alerts
|

The Transcriptome and DNA Methylome Landscapes of Human Primordial Germ Cells

Abstract: Germ cells are vital for transmitting genetic information from one generation to the next and for maintaining the continuation of species. Here, we analyze the transcriptome of human primordial germ cells (PGCs) from the migrating stage to the gonadal stage at single-cell and single-base resolutions. Human PGCs show unique transcription patterns involving the simultaneous expression of both pluripotency genes and germline-specific genes, with a subset of them displaying developmental-stage-specific features. F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

52
598
3
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 535 publications
(678 citation statements)
references
References 46 publications
52
598
3
2
Order By: Relevance
“…The germ lineage also bears a unique developmentally regulated state, with transient erasure of genomic imprints that ensues from a post-inner cell mass wave of methylome erasure (Tada et al 1998), followed by the establishment of male or female gametic epigenetic sexual dimorphism required for physiological reproduction (Gkountela et al 2015;Guo et al 2015;Tang et al 2015). Thus a recognized molecular distinction between PGC and precursor and downstream states is the erasure of all genomic imprints.…”
mentioning
confidence: 99%
“…The germ lineage also bears a unique developmentally regulated state, with transient erasure of genomic imprints that ensues from a post-inner cell mass wave of methylome erasure (Tada et al 1998), followed by the establishment of male or female gametic epigenetic sexual dimorphism required for physiological reproduction (Gkountela et al 2015;Guo et al 2015;Tang et al 2015). Thus a recognized molecular distinction between PGC and precursor and downstream states is the erasure of all genomic imprints.…”
mentioning
confidence: 99%
“…4C). This heterogeneity in the expression of germline markers is also observed in early stage PGCs both in mouse 7, 83 and human 84, and may be a general characteristic of pPGCs and PGCs. Investigating the expression and localization of additional germ plasm markers, including DND1, TDRD, NANOS and PIWI 26, 85, 86, 87, would help clarify the presence of germ plasm in chicken.…”
Section: A Historical Perspective On Avian Pgcs: Is Maternal Specificmentioning
confidence: 70%
“…Both high‐throughput genome‐wide single‐cell transcriptomics and methylomics are fast evolving techniques 50, 84 that will allow a detailed molecular analysis and comparison between species that will lead to a clarification on the modality of pPGC and PGC formation.…”
Section: Mode Of Formation: Pgcs or Ppgcs?mentioning
confidence: 99%
“…Recently, three groups independently reported genome-wide DNA methylation and transcription profiles of hPGCs obtained from aborted embryos at the stages of arrival of the hPGCs to-and proliferation/differentiation within-the genital ridges (corresponding to E9.5-E13.5 in mice) (Gkountela et al 2015;Guo et al 2015;Tang et al 2015), and revealed fundamental similarities in epigenome reprogramming between humans and mice. These discoveries have posed several critical challenges for the future.…”
Section: Perspectivementioning
confidence: 99%